Procedural and Physical Interventions for Vaccine Injections: Systematic Review of Randomized Controlled Trials and Quasi-Randomized Controlled Trials. (October 2015) - Taddio, Anna; Shah, Vibhuti; McMurtry, C. Meghan; MacDonald, Noni E.; Ipp, Moshe; Riddell, Rebecca Pillai; Noel, Melanie; Chambers, Christine T.
Abstract : Background: This systematic review evaluated the effectiveness of physical and procedural interventions for reducing pain and related outcomes during vaccination. Design/Methods: Databases were searched using a broad search strategy to identify relevant randomized and quasi-randomized controlled trials. Data were extracted according to procedure phase (preprocedure, acute, recovery, and combinations of these) and pooled using established methods. Results: A total of 31 studies were included. Acute infant distress was diminished during intramuscular injection without aspiration (n=313): standardized mean difference (SMD) −0.82 (95% confidence interval [CI]: −1.18, −0.46). Injecting the most painful vaccine last during vaccinations reduced acute infant distress (n=196): SMD −0.69 (95% CI: −0.98, −0.4). Simultaneous injections reduced acute infant distress compared with sequential injections (n=172): SMD −0.56 (95% CI: −0.87, −0.25). There was no benefit of simultaneous injections in children. Less infant distress during the acute and recovery phases combined occurred with vastus lateralis (vs. deltoid) injections (n=185): SMD −0.70 (95% CI: −1.00, −0.41). Skin-to-skin contact in neonates (n=736) reduced acute distress: SMD −0.65 (95% CI: −1.05, −0.25). Holding infants reduced acute distress after removal of the data from 1 methodologically diverse study (n=107): SMD −1.25 (95% CI: −2.05, −0.46). Holding after vaccination (n=417) reduced infant distress during the acute and recovery phases combined: SMD −0.65 (95% CI: −1.08, −0.22). Self-reported fear was reduced for children positioned upright (n=107): SMD −0.39 (95% CI: −0.77, −0.01). Non-nutritive sucking (n=186) reduced acute distress in infants: SMD −1.88 (95% CI: −2.57, −1.18). Manual tactile stimulation did not reduce pain across the lifespan. An external vibrating device and cold reduced pain in children (n=145): SMD −1.23 (95% CI: −1.58, −0.87). There was no benefit of warming the vaccine in adults. Muscle tension was beneficial in selected indices of fainting in adolescents and adults. Conclusions: Interventions with evidence of benefit in select populations include: no aspiration, injecting most painful vaccine last, simultaneous injections, vastus lateralis injection, positioning interventions, non-nutritive sucking, external vibrating device with cold, and muscle tension. Abstract : Supplemental Digital Content is available in the text.